The effect of warm water on the spasticity of the cerebral paralyzed child - E. Basson; A. Boonzaaier; A. Fourie; M. Eisenberg (AOSIS, 2000)
This study investigated the effect of warm water on spasticity in children with cerebral palsy. The sample was taken from the population of spastic cerebral palsy children at Bel Porto School. Ten children who met the inclusion criteria were randomly selected. The methodology included an assessment of each child's spasticity according to the Motor Assessment Scale(MAS). Two variables were tested prior to and after the child was exposed to warm water. These were the distance each child could reach and the time it took to passively lengthen the biceps muscle. The exposure to warm water was 15 minutes long at a temperature of 31 degrees C. Measurements were taken for both arms and a more affected and a less affected arm were identified. The data were analysed using the Wilcoxon Sign-Ranked Test (<0,05). The percentage improvement for each arm was computed. The results showed a significant improvement in both the reach distance and the time it took to passively lengthen biceps for both arms.